Nonlinear Quasi-Classical Model of Isothermal Relaxation Polarization Currents in Functional Elements of Microelectronics, Optoelectronics, and Fiber Optics Based on Crystals with Ionic-Molecular Chemical Bonds with Complex Crystalline Structure; Crystals; Vol. 15, iss. 10 - Kalitka V. Valery; Mekhtiev A. D. Ali Dzhavanshirovich; Neshina E. G. Elena Gennadjevna; Yurchenko A. V. Aleksey Vasilievich; Alkina A. D. Aliya Dauletkhanovna; Bulatbaev F. N. Feliks Nazymovich; Issaev V.; Makhanov K. M.; Lukin D.; Kayumov D. Damir; Zaplakhov A. (2025, 2025)
Title screen